in Digital Logic edited by
10,606 views
45 votes
45 votes

Let $\oplus$ denote the exclusive OR (XOR) operation. Let '$1$' and '$0$' denote the binary constants. Consider the following Boolean expression for $F$ over two variables $P$ and $Q$:

$$F(P,Q)=\left( \left(1 \oplus P \right) \oplus \left( P \oplus Q \right )\right ) \oplus \left(\left(P \oplus Q\right) \oplus \left(Q \oplus 0\right)\right)$$

The equivalent expression for $F$ is

  1. $P+Q$
  2. $\overline{P+Q}$
  3. $P \oplus Q$
  4. $\overline {P \oplus Q}$
in Digital Logic edited by
10.6k views

3 Comments

As ⊕ is commutative and associative operator, so we can remove all the parentheses if required, and apply the following three properties
1. x⊕x = 0
2. 0⊕x = x
3. 1⊕x= x'

Answer will be (D)

26
26
This help so much to simplify expression
1
1

Adding more to @Manu Thakur’s comment:-

$\implies \overline {\left( P \oplus Q\right)} =  {\left( P’ \oplus Q\right)} = {\left( P \oplus Q’\right)}=  {\left( P \odot Q\right)} = {\left( P’ \odot Q’\right)}$

1
1

7 Answers

58 votes
58 votes
Best answer
XOR is associative and commutative. Also, $A \oplus A = 0$ and $A \oplus 1 = \overline{ A}$ and $A \oplus 0 = A$.  So
$\left( \left(1 \oplus P \right) \oplus \left( P \oplus Q \right )\right ) \oplus \left(\left(P \oplus Q\right) \oplus \left(Q \oplus 0\right)\right)$
$\implies \left(1 \oplus P \right) \oplus \left( \left( P \oplus Q \right ) \oplus \left(P \oplus Q \right) \right) \oplus \left(Q \oplus 0\right)$
$\implies  \left(1 \oplus 0 \right) \oplus \left( P \oplus Q \right) $
$\implies 1 \oplus \left(  P\oplus Q \right)$
$\implies \overline {\left( P \oplus Q\right)}$

Correct Answer: $D$
edited by
by

4 Comments

@Meghna yes, it is correct.

@Syed Yes, $A \oplus A = 0,$ here $A = (P \oplus Q)$
1
1
It is such a relief to not have to expand the options. -_-
0
0
Sir but A (EXOR) 1 = A’ or A only ?
0
0
13 votes
13 votes

D)
Since there are only 2 variables putting in pair of values of P and Q in F and checking with the options is a time saving method.
But Lets solve it.


 

8 votes
8 votes

Using the properties of associativity and commutativity, and the below mentioned properties we can find the correct answer:

1. $X⊕X = 0$

2. $X⊕1=X'$

3. $X⊕0=X$


$F(P,Q)=((1⊕P)⊕(P⊕Q))⊕((P⊕Q)⊕(Q⊕0))$

$=(P'⊕(P⊕Q))⊕((P⊕Q)⊕(Q⊕0))$

$=((P'⊕P)⊕Q))⊕((P⊕Q)⊕(Q⊕0))$

$=((1⊕Q)⊕((P⊕Q)⊕(Q⊕0))$

$=(Q'⊕((P⊕Q)⊕(Q⊕0))) $

$=(Q'⊕((P⊕Q)⊕Q)) $

$=(Q'⊕(P⊕(Q⊕Q))) $

$=(Q'⊕(P⊕0)) $

$=(Q'⊕P) $

$=(Q⊕P)'$

So, the correct option is, option no. D.

edited by
6 votes
6 votes

Alternatively, You can follow this approach too:

1 comment

exactly the way I did...
0
0
Answer:

Related questions